From Fandom to Social Movement: Indonesian NCTzen’s Reception of the NCT x Starbucks Boycott - Nur, Aqila Naila; Kusuma, Rina Sari (Jogjakarta Communication Conference (JCC), 2025)
This research aims to analyze the reception of NCT fans (NCTzen) in Indonesia towards the boycott of the collaboration between K-pop idol NCT and Starbucks, which occurred in the context of the boycott movement of products affiliated with Israel. The collaboration is seen as ignoring the ongoing social context. Where K-pop fans, especially NCTzen, show a high level of sensitivity to social issues and have high expectations of their idols and the brands they collaborate with. This research used a qualitative approach with an in-depth interview with NCT fans in Indonesia. The snowball sampling technique was used to select respondents based on certain criteria, such as religious background, status as a student or worker, and fandom community involvement. The research used Stuart Hall's theory of reception analysis, which includes three leading positions: dominant hegemonic position, negotiated position, and oppositional position. The interviews showed the dominance of positive reactions from fans to the boycott movement and the dominance of negative reactions to the collaboration, as well as changes in supporting their idols after the collaboration contract ended. The results of this study indicate that fans' reception of individual backgrounds can influence their attitudes towards idols and collaborating brands. This confirms that K-pop fandom is not just an entertainment community, but also has a high social awareness. This study also highlights the importance of considering social contexts in marketing strategies, especially in collaborations between celebrities and global brands.